2013
DOI: 10.1038/ismej.2013.91
|View full text |Cite
|
Sign up to set email alerts
|

Carbon availability triggers the decomposition of plant litter and assimilation of nitrogen by an ectomycorrhizal fungus

Abstract: The majority of nitrogen in forest soils is found in organic matter–protein complexes. Ectomycorrhizal fungi (EMF) are thought to have a key role in decomposing and mobilizing nitrogen from such complexes. However, little is known about the mechanisms governing these processes, how they are regulated by the carbon in the host plant and the availability of more easily available forms of nitrogen sources. Here we used spectroscopic analyses and transcriptome profiling to examine how the presence or absence of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 55 publications
4
78
0
1
Order By: Relevance
“…Specifically, peroxidase activity correlated positively with the ratio of ectomycorrhizal to saprotrophic diversity, whereas cellobiohydrolases showed the reverse trend, correlating positively with the ratio of saprotrophic to ectomycorrhizal diversity (Dataset S1). These observations are consistent with the classical notion of saprotrophs as principal degraders of readily available carbon, as well as recent hypotheses that ectomycorrhizal fungi target nutrients bound in complex soil organic matter (49,50). Because species-level composition of fungal communities does not correlate strongly with enzyme activity at the scale of this study, functional trait or phylogenetic approaches targeting key resource acquisition strategies may offer a better predictive framework for understanding fungal function across systems that have few species in common.…”
Section: Resultssupporting
confidence: 75%
“…Specifically, peroxidase activity correlated positively with the ratio of ectomycorrhizal to saprotrophic diversity, whereas cellobiohydrolases showed the reverse trend, correlating positively with the ratio of saprotrophic to ectomycorrhizal diversity (Dataset S1). These observations are consistent with the classical notion of saprotrophs as principal degraders of readily available carbon, as well as recent hypotheses that ectomycorrhizal fungi target nutrients bound in complex soil organic matter (49,50). Because species-level composition of fungal communities does not correlate strongly with enzyme activity at the scale of this study, functional trait or phylogenetic approaches targeting key resource acquisition strategies may offer a better predictive framework for understanding fungal function across systems that have few species in common.…”
Section: Resultssupporting
confidence: 75%
“…They are portrayed as mutualists trading host photoassimilates for nutrients and having limited capacity to decompose soil lignocellulose 1-3 , as a result of their reduced repertoire of PCWDEs 4-6 . However, recent studies are challenging this view [7][8][9][10] . An improved understanding of the ability of ECM fungi to decompose lignocellulose is needed to resolve mechanisms of nutrient cycling in forests.…”
Section: E T T E R Smentioning
confidence: 99%
“…Gene tree-species tree reconciliations of LPMOs and other decay-related CAZymes suggest that parallel losses of brown-rot saprotrophy have occurred in the three ECM lineages in Boletales (Boletineae, Suillineae and Sclerodermatineae; Supplementary Figs. 15-23), although the ability to oxidize organic matter remains in Paxillus involutus 9 .…”
mentioning
confidence: 99%
“…The most abundant CAZyme family acting on the plant cell wall in the genome of L. bicolor is LPMO (7). P. involutus has a unique enzymatic system, similar to that of brown rot fungi, to decompose plant biomass (78,79). Transcriptomic studies of P. involutus have revealed that only one ␤-1,4-endoglucanase (GH9) and two LPMO genes are expressed during growth on plant litter or cellulose (79).…”
Section: Ectomycorrhizal Fungimentioning
confidence: 99%